2023
DOI: 10.3389/fpubh.2022.986026
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of chronic rhinosinusitis among Chinese: A systematic review and meta-analysis

Abstract: BackgroundChronic rhinosinusitis (CRS) can be seen in people of all ages. CRS heavily affects the quality of a patient's daily life and also causes tremendous economic burdens on patients' families and society. The prevalence of CRS in different countries varies and no systematic review of the prevalence of CRS among Chinese has been published previously. The objective of this systematic review and meta-analysis is to determine the prevalence of CRS among Chinese and to explore the main risk factors of CRS amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…Apart from molecular mechanisms contributing to CHD development, conditions such as obesity and asthma are commonly associated with CHD or CRS [24][25][26][27]. The advancement of CHD may be associated with the severity of subsequent CRS, and this is attributable to their similar pathophysiology and associated comorbidities [17,[24][25][26][27][28]. Our findings support this possible association.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Apart from molecular mechanisms contributing to CHD development, conditions such as obesity and asthma are commonly associated with CHD or CRS [24][25][26][27]. The advancement of CHD may be associated with the severity of subsequent CRS, and this is attributable to their similar pathophysiology and associated comorbidities [17,[24][25][26][27][28]. Our findings support this possible association.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, CRS involves local aggregation of immune cells such as eosinophils, natural killer cells, and neutrophils in nasal polyps [23]. Apart from molecular mechanisms contributing to CHD development, conditions such as obesity and asthma are commonly associated with CHD or CRS [24][25][26][27]. The advancement of CHD may be associated with the severity of subsequent CRS, and this is attributable to their similar pathophysiology and associated comorbidities [17,[24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of the risk factors for CRS in the Chinese population revealed that individuals residing in urban areas exhibited a lower prevalence of CRS [ 37 ]. However, other reports have focused on the impact of environmental factors, including air pollution, on CRS development [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These figures are lower than the prevalence rates reported in other countries, which typically range from 5.5% to 12%. 1,[7][8][9] Among the participants who qualified for symptom-based CRS, only 6 individuals underwent nasal endoscopy and were confirmed as having CRS, resulting in a prevalence of 0.58% for endoscopy-based CRS. However, if all 20 participants who qualified for symptom-based CRS had undergone nasal endoscopy and were positive, the prevalence could have been as high as 2.53%.…”
Section: Discussionmentioning
confidence: 99%